Sleep problems in a Down syndrome population. Issue 4 (11th September 2008) - Carter, M; McCaughey, E; Annaz, D; Hill, C M
Abstract : Objective: To determine the prevalence of sleep problems in children with Down syndrome. Design and setting: A community prevalence study in a child population of 100 000 in England. Participants: 58 children with Down syndrome aged to 0.65–17.9 years (mean 8.6 years). Interventions: Child sleep Habits Questionnaire. Results: Compared to published data for typically developing populations, children with Down syndrome were reported to have significantly greater bedtime resistance, sleep anxiety, night waking, parasomnias, sleep disordered breathing and day-time sleepiness. Amongst children 4 years and older, 66% rarely fell asleep in their own beds, 55% were always restless during sleep and 40% usually woke at least once during the night. Importantly, 78% seemed tired during the day at least 2 days per week, suggesting inadequate sleep. Conclusions: Parents report universal sleep problems in school aged children with Down syndrome. Paediatricians should routinely enquire about sleep behaviour in these children.